Monday

September 1, 2014

September 1, 2014

Posted by **Camren** on Wednesday, April 17, 2013 at 9:35pm.

- Math -
**Reiny**, Wednesday, April 17, 2013 at 10:47pm4x - 1 - 2x - 2 = 3x - 4x - 2

-x = 1

x = -1

**Answer this Question**

**Related Questions**

Math.stat help :( - Consider the following hypothesis statement using alpha = ....

math - Consider the following hypothesis statement using alpha = .05, and data ...

Algebra - Based on surveys conducted in your area, you determine that it is ...

algebra for business - As an entrepreneur, there are going to be many decisions...

calculus - The efficiency of an internal combustion engine is given by E= (1-v/V...

calculus - The efficiency of an internal combustion engine is given by E= (1-v/V...

MATH PLEASE CHECK IT!!2 - m-2/m-5*m+5/m-2=-1 If your problem is this: (m - 2)/(m...

Calculus (for Business) - Suppose a fish swimming a distance of L ft at a speed ...

algebra 2 - The annual expenses of a manufacturing company must satisfy the ...

Math - If 6 is increased by 4 times a number, the result is 68. A.Write and ...